The Factors of Academic Achievement - Thankam Varghese, Soumya; Rathnasabapathy, Maya (International Journal of Psychosocial Rehabilitation, 2020)
The present study is trying to understand the factors behind the academic outcomes of students when they are affected by blindness or related problems. Intelligence, aspects of identity, and self-esteem of 500 students having blindness or related problems have been analyzed in relation to their academic performance. The variables intelligence, aspects of identity, and self-esteem are showing a weak relationship with academic performance. The regression coefficient of intelligence is also not significantly predicting the academic performance. Intelligence, aspects of identity, and self-esteem could influence and enhance the academic performance of children with visual impairment to an extent, but there are factors that are detrimental to the academic performance apart from this too.